2002
DOI: 10.1002/jat.836
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the highest no‐effect dose (HNED) and of the elimination pattern for cocaine in horses

Abstract: Cocaine is one of the most widespread illegal stimulants utilized by the human population throughout the world. The aim of this study was to establish the highest no-effect dose (HNED) of cocaine on the spontaneous locomotor activity (SLA) of horses in a behavior chamber, and thereby to determine the maximal acceptable threshold of the urinary drug concentration in horses. Twelve English thoroughbred mares received 0.02, 0.03, 0.04, 0.08 or 0.12 mg kg(-1) cocaine i.v. or saline solution (control). It was noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…It is also possible that this decrease in heart rate was actually related to the alcohol vehicle in which the cocaine was dissolved, as no vehicle control was included in the study. These results are notably different from those obtained by Queiroz‐Neto et al ., who found that intravenous doses as small as 0.03 mg/kg (approximately 15 mg for a 500 kg horse) produced notable, albeit subjective, behavioral changes, such as head tossing and neighing. Although the behavioral assessments in the present study were also subjective, the lack of any prolonged effect on heart rate following administration of the 50 mg dose of cocaine was consistent with a lack of behavioral effects, as one would generally expect some increase in heart rate to be associated with any significant degree of CNS stimulation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It is also possible that this decrease in heart rate was actually related to the alcohol vehicle in which the cocaine was dissolved, as no vehicle control was included in the study. These results are notably different from those obtained by Queiroz‐Neto et al ., who found that intravenous doses as small as 0.03 mg/kg (approximately 15 mg for a 500 kg horse) produced notable, albeit subjective, behavioral changes, such as head tossing and neighing. Although the behavioral assessments in the present study were also subjective, the lack of any prolonged effect on heart rate following administration of the 50 mg dose of cocaine was consistent with a lack of behavioral effects, as one would generally expect some increase in heart rate to be associated with any significant degree of CNS stimulation.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are consistent with a recent study that indicated that a 10 mg dose of cocaine administered i.v. resulted in quantifiable concentrations of BZE by LC–MS analysis in urine samples collected 24 h after administration (Queiroz‐Neto et al. , 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Logan, UT-USA) connected to a computer. 19 SLA was calculated from data registered in the computer as the mean of interruptions every 10 minutes.…”
Section: Methodsmentioning
confidence: 99%